Examining the Factors Affecting the Digital Supply Chain in the Food Retail Industry - Samadi Vik, Hossein; Sanavifard, Rasoul; Khajeh, Mostafa (Management Strategies and Engineering Sciences, 2025)
The present study aims to examine the factors affecting the digital supply chain in the food retail industry. In terms of purpose, the research is applied, and in terms of data collection, it follows a mixed-methods (qualitative-quantitative) approach. The statistical population in the qualitative phase includes professors, experts in technology and supply chain management, and senior managers in production and research and development within the online food retail industry. In the quantitative phase, the statistical population consists of all managers and employees of online supermarkets in Tehran. The sample size in the qualitative phase was determined based on theoretical saturation (10 participants) using purposive sampling, while in the quantitative phase, a sample of 380 participants was selected through stratified random sampling. Data collection tools included interviews in the qualitative phase and a researcher-developed questionnaire in the quantitative phase. The validity of the questionnaire was confirmed through face and content validity by several experts, convergent validity was verified by calculating the average variance extracted (AVE), and discriminant validity was assessed through the square root of AVE. The reliability of the questionnaire was established using Cronbach’s alpha, which yielded a value of 0.898 for the entire instrument. Data analysis was performed using SmartPLS 3 software. Among the 29 available indicators (items), seven main components were identified. The results indicated that economic factors, social factors, technological factors, environmental factors, managerial factors, organizational factors, and industrial factors were recognized as causal conditions influencing the digital supply chain in the food retail industry. Additionally, the model fit was also evaluated.